FACTORS AFFECTING THE INTENTION TO PURCHASE ORGANIC VEGETABLES WITH THEORY PLANNED BEHAVIOUR APPROACH - Septiadinur Rejeki; Novil Dedy Andriatmoko; Hery Toiba (Agricultural Socio-Economics Journal, 2021)
The recent modern healthy lifestyle is influenced by the selection of food ingredient such as organic vegetables. Organic vegetables are well known in community. But, the purchase of organic vegetables has decreased in the last few years because price has been high, packaging and quality have not been interesting, and low priority on organic vegetables than conventional vegetables. This research was conducted by the Theory Planned Behaviour (TPB) approach with 6 variables. Those are price, packaging, quality, attitude, subjective norms, and perceived behavioral control to analyze the effect of factor to the decreased purchase attitude and intention buy organic vegetables with Structural Equation Model (SEM)-Partial Least Square (PLS) analysis. The results showed that the following factors are price, quality, attitude, subjective norms, and perceived behavioral control have an effect to the decreased purchase attitude and intention buy organic vegetables. So, it can be a strategy for selling and consuming organic vegetables in the future.